Comparative analysis of startup ecosystems in the development models of Eastern European countries: experience for the post-war reconstruction of Ukraine - Antoniuk, Dmytro; Antoniuk, Kateryna (Management and Entrepreneurship: Trends of Development, 2023)
Preservation and reconstruction of the start-up industry based on the modernization of the start-up ecosystem can be a powerful incentive for the restoration of the country’s scientific and technical potential in conditions of huge human, economic and infrastructural losses. A thorough analysis of the key components of the startup support ecosystem, the problems of their formation and development allowed us to form a hypothesis about the feasibility of using the experience of Eastern European countries and its adaptation to the socio-economic and political conditions of Ukraine. The research involved the use of methods of theoretical generalization, dialectics, analysis and systematization, grouping, and desk research. The article substantiates the conceptual directions of improving the startup ecosystem of our country at the stage of its post-war recovery, namely: stimulating innovation and creating a favorable institutional environment, forming a culture of entrepreneurship, in particular within the youth, improving the institutional infrastructure of startup support, attracting global partners and external investments, modernizing the information space and ensuring data protection. JEL Classification: L26, M13, O44.